(untitled) (Research, Society and Development, 2021)
The objective of this work was to evaluate the application of plant regulators and biofertilizers in the development of cladodes segments and formation of seedlings of the species Selenicereus setaceus. The experiment was set up in a 5x4x7 factorial scheme, 5 treatments: biofertilizers, auxin 500 ppm, gibberellin 100 ppm, cytokinin 200 ppm and control. Four cladodes fractions: apical segment, median segment, basal segment (10 cm) and whole cladodes (40 cm) and seven evaluation periods, 0, 20, 39, 64, 91, 116 and 143 days after planting. The cladodes treated with auxin presented higher mean lengths of root and dry matter, while those treated with biofertilizer showed lower ones. The root dry mass of whole cladodes (40 cm) was higher than that observed for segregated regions of cladodes. The treatments with whole cladode and basal region presented higher average number of shoots compared to the median and apical regions. The auxin and cytokinin treatments promoted a greater number of sprouts in the cladodes. The longer sprouting length is observed for treatment with whole cladodes.